A questionnaire-based study of the effect of driving style on the acceptance of active driving guidance - Xiang, Wang; Qiu, Yi; Xing, Lu; He, Yanjie (Scientific reports, 2025)
Active driving guidance functions are becoming increasingly prevalent in vehicles. In order to understand the demand characteristics, risk-benefit concerns and value judgments of different styles of drivers on active driving guidance, this paper focuses on the influence of driving style on the acceptance of active driving guidance. Based on the online questionnaire data, we use the extended model of technology acceptance and the concept of trust heuristic as the basic theory, divide the dimensions of driving styles, introduce the variables to measure acceptance, and construct a "driving style-active driving guidance acceptance" mental model by applying structural equation modeling (SEM).This model was constructed using SEM to clarify the association between different driving styles and the degree of acceptance of active driving guidance. The results showed that adventurous and angry drivers were significantly less receptive to active driving incentives; conservative drivers were significantly more receptive to active driving incentives; distracted drivers were more considerate of the conditions and popularity of active driving incentives; and anxious drivers were more sensitive to the perceived risk of active driving incentives and were less receptive to active driving incentives. The results of the study provide a basis for the development and promotion of new intelligent driving technologies such as active driving guidance.